Borehole electric log from the southern sector of Larsen C Ice Shelf, Antarctic Peninsula, December 2022 ... - Hubbard, Bryn; Miles, Katie; RiPIce Project Team (NERC EDS UK Polar Data Centre, 2024)
This is an electric log of a borehole drilled by hot water to 120 m (Site 1) on Larsen C Ice Shelf, Antarctic Peninsula. The borehole was drilled in December 2022 to investigate the internal properties of a suture zone (Site 1) and a meteoric ice band (Site 2) of an ice shelf, as part of the NERC-funded RiPIce (Rift Propagation for Ice sheet models) research project. NERC standard grant NE/T008016/1. ... : The dataset is an electric log from a borehole drilled to 120 m (Site 1) on Larsen C Ice Shelf, Antarctica, in December 2022. It was acquired using a slim-hole electric borehole probe manufactured by Robertson Geologging Ltd, which is comprised of a source electrode that emits a low-frequency bi-directional electric current. Boreholes were logged whilst the electric probe was travelling up the borehole. ...